EXPLORING TRANSITIVITY SYSTEM IN “THE FAIRY TULIP” LEARNERS TEXTBOOK - Ulya . Muharrami (Universitas Negeri Medan, 2023)
This study deals with transitivity system in narrative text titled “The Fairy Tulip” of grade IX Junior High School in learners textbook. The aims of this research are to identify the transitivity constructions and to describe the most frequency process types in narrative entitled “The Fairy Tulip” in learners textbook (Communicative English in Context), Grade IX Junior High School. This research was conducted by qualitative descriptive method. The data was the narrative text titled “The Fairy Tulip”. The technique for data collection was content analysis. The data was analyzed by count down the number of sentences; count down the number of clauses; generate clause identification by using transitivity analysis; generate the degrees of frequency for each transitivity element; and describe the connectedness of the entire clauses for the purpose in narrative text titled “The Fairy Tulip”. The result shows that there are six types of processes in the narrative text, those are: (1) material process (60%), (2) mental process (20%), (3) relational process (10%), (4) behavioral process (5%), and (5) existential process (5%). Material process is the dominant process. There are seven types of the participants, namely actor, goal, senser, phenomenon, attribute, token, and existent. The most dominant participant is material’s participants (38,89%). The most dominant circumstance is circumstance of place (43,75%).